So-called bifocal tumors with diabetes insipidus and negative tumor markers: are they all germinoma?. Issue 2 (20th August 2020) - Kanamori, Masayuki; Takami, Hirokazu; Yamaguchi, Shigeru; Sasayama, Takashi; Yoshimoto, Koji; Tominaga, Teiji; Inoue, Akihiro; Ikeda, Naokado; Kambe, Atsushi; Kumabe, Toshihiro; Matsuda, Masahide; Tanaka, Shota; et al.
Abstract: Background: The Delphi consensus statements on the management of germ cell tumors (GCTs) failed to reach agreements on the statement that the cases with (i) pineal and neurohypophyseal bifocal lesion, (ii) with diabetes insipidus, and (iii) with negative tumor markers can be diagnosed as germinoma without histological verification. To answer this, multicenter retrospective analysis was performed. Methods: A questionnaire on clinical findings, histological diagnosis, and details of surgical procedures was sent to 86 neurosurgical and 35 pediatrics departments in Japan. Results: Fifty-one institutes reported 132 cases that fulfilled the 3 criteria. Tissue sampling was performed in 91 cases from pineal ( n = 44), neurohypophyseal ( n = 32), both ( n = 6), and distant ( n = 9) lesions. Histological diagnosis was established in 89 cases: pure germinoma or germinoma with syncytiotrophoblastic giant cells in 82 (92.1%) cases, germinoma and mature teratoma in 2 cases, and granulomatous inflammation in 2 cases. Histological diagnosis was not established in 2 cases. Although no tumors other than GCTs were identified, 3 (3.4%) patients had non-germinomatous GCTs (NGGCTs). None of the patients developed permanent complications after endoscopic or stereotactic biopsy. Thirty-nine patients underwent simultaneous procedure for acute hydrocephalus without permanent complications, and hydrocephalus was controlled in 94.9% of them. Conclusion: All patients who fulfilled the 3 criteria had GCTs or granulomatous inflammation, but not other types of tumors. However, no fewer than 3.4% of the patients had NGGCTs. Considering the safety and the effects of simultaneous procedures for acute hydrocephalus, biopsy was recommended in such patients.